Studies in symbolic interaction. Vol. 39 - Denzin, Norman K. (Bingley, U.K. : Emerald, 2012)
Part I, "Theoretical Openings," of Volume 39 of Studies in Symbolic Interaction contains outstanding contributions by leading interactionists on welfare reform, history, biography and memory. The three chapters in Part II, "Studies in Social Construction," interrogate the complexities of social interaction, interpersonal and professional identity, and the cinematic representation of alcoholism. Part III takes up important interpretive interventions on the topics of imagination and intimate deception in everyday life.
The mesodomain of welfare reform : renegotiating the order of economic inequality / Mark A. Covaleski, Mark W. Dirsmith, Jane Weiss -- Milkshakes and convertibles : an autobiographical reflection / Sara Delamont -- The superiority delusion and critical consciousness : the paradox of role-taking refusal in the microfoundation of dehumanization and resistance / Gil Richard Musolf -- Collective identity narratives : historical and emergent stories of selfhood in a deindustrializing community / Lawrence T. Nichols, Jason Rine -- Never mind the scholar, here's the old punk : identity, community, and the aging music fan / Andrew F. Herrmann -- Compliance dramas in Alcoholic Anonymous films : an interactionist reading of The days of wine and roses / Michael A. Katovich -- Interactions and the drama of engagement / Robert S. Perinbanayagam, E. Doyle McCarthy -- Imagining imagination / John M. Johnson ... [et al.] -- Intimate deception in everyday life / Susie Scott.
Keywords: Social Science -- Sociology -- General; Social Science -- General; Society & social sciences; Social interaction; Symbolic interactionism